Effect of Infills on the Response Modification Factor for Infilled Reinforced Concrete Frame Buildings - Dina Hesham Helmy; Hussein Okail; Mostafa Zidan (Civil Engineering Journal, 2023)
RC frames with unreinforced masonry infill walls are the most common type of building. Unreinforced masonry walls are often not considered by engineers in the design process, although walls and frames interact during strong ground motion, leading to structural responses deviating radically from what is expected in the design. Under lateral load, reinforced concrete confining members (frames) act in tension or compression, depending on the direction of the lateral seismic pressures. Meanwhile, masonry walls act as diagonal struts prone to compression. This research aims to develop the effect of masonry infills and their distribution on the value of the resulting response modification factor. For this purpose, a parametric study was performed on five, seven, and ten-story' buildings modeled as bare and infilled frames. Infill ratio, panel aspect ratio, unidirectional eccentricity, and bidirectional eccentricities were the parameters investigated. Each proposed model's resulting response modification factor was compared to the value cited in different international codes. It was concluded that this value differs depending on several parameters and cannot be constant for a certain structural system. The novelty of this research is the deduction of a general equation to calculate the response modification factor as a function of the percentage of infills and the eccentricity, while presenting two different methods to calculate it. Doi: 10.28991/CEJ-2023-09-12-09 Full Text: PDF